Processing of Bimetallic Inconel 625-16Mo3 Steel Tube via Supercritical Bend: Study of the Mechanical Properties and Structure - Barenyi, Igor; Slany, Martin; Kouril, Karel; Zouhar, Jan; Kolomy, Stepan; Sedlak, Josef; Majerik, Jozef (Materials (Basel, Switzerland), 2023)
Incineration is currently the standard way of disposing of municipal waste. It uses components protected by high-temperature-resistant layers of materials, such as Inconel alloys. Therefore, the objective of the current paper is to study the mechanical properties and structure of a bimetallic Inconel 625-16Mo3 steel tube. The Inconel 625 layer was 3.5 mm thick and was applied to the surface of the tube with a wall thickness of 7 mm via the cold metal transfer method. The bimetallic tube was bent using a supercritical bend (d ≤ 0.7D). This paper is focused on the investigation of the material changes in the Inconel 625 layer areas influenced by the maximum tensile and compressive stresses after the bend. The change in layer thickness after the bend was evaluated and compared to the non-deformed tube. In addition, the local mechanical properties (nanohardness, Young modulus) across the indicated interfacial areas using quasistatic nanoindentation were investigated. Subsequently, a thorough microstructure observation was carried out in areas with maximum tensile and compressive stresses to determine changes in the morphology and size of dendrites related to the effect of tensile or compressive stresses induced by bending. It was found that the grain featured a stretched secondary dendrite axis in the area of tensile stress, but compressive stress imparted a prolongation of the primary dendrite axis.
Keywords: welding; Inconel 625; bimetallic material; mechanical properties; microstructure; supercritical bend